Teachers’ Perspectives On Developing Collaborative Skills In Indonesian Elementary Students: A Qualitative Study - Setiawan, Dadan; Maftuh, Bunyamin; Syaodih, Ernawulan; Riyadi, Arie Rakhmat (International Conference on Elementary Education, 2025)
This study explores elementary students’ collaborative skills from both student and teacher perspectives, with a focus on group interaction dynamics and pedagogical strategies that promote effective collaboration. The qualitative study was conducted in four elementary schools in Cirebon Regency, involving 24 students and four teachers. Data were collected through classroom observations,semi-structured interviews, and learning document analysis. Findings indicate that students perceive collaboration as task-sharing, mutual support, and joint decision-making in classroom projects. Key challenges include differences in abilities, individual dominance, and uneven group coordination. Teachers emphasized the importance of strategic planning, facilitation of interactions, establishment of group norms, and continuous feedback to optimize collaboration. The results highlight that collaborative skills develop through active pedagogy, consistent teacher monitoring, and the habituation ofcollaborative practices in daily learning activities. This study provides significant insights for designing systematic and measurable learning strategies aimed at enhancing elementary students’ collaborative competencies, offering practical implications for teachers and educational policymakers.